2013
DOI: 10.1097/qai.0b013e3182965d45
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity, Safety, and Pharmacokinetics/Pharmacodynamics of Tenofovir Alafenamide as 10-Day Monotherapy in HIV-1–Positive Adults

Abstract: Compared with 300 mg TDF, TAF demonstrated more potent antiviral activity, higher peripheral blood mononuclear cell intracellular tenofovir diphosphate levels, and lower plasma TFV exposures, at approximately 1/10th of the dose. This may translate into greater antiviral efficacy, a higher barrier to resistance, and an improved safety profile relative to TDF, supporting further investigation of TAF dosed once daily in HIV-infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
275
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 282 publications
(293 citation statements)
references
References 10 publications
17
275
0
1
Order By: Relevance
“…In clinical studies, TAF has demonstrated favorable pharmacological properties, with higher intracellular levels of TFV-DP and lower circulating levels of TFV than of TDF. The higher TFV-DP levels in peripheral blood mononuclear cells (PBMCs) have resulted in improved antiviral activity at lower doses than TDF in monotherapy studies (11,12). The efficacy of low doses of TAF has been confirmed in phase 2 clinical trials in combination with elvitegravir (EVG, or E), cobicistat (COBI, or C), and emtricitabine (FTC, or F).…”
Section: T Enofovir [(R)-9-(2-phosphonomethoxypropyl)adenine] (Tfv)mentioning
confidence: 87%
“…In clinical studies, TAF has demonstrated favorable pharmacological properties, with higher intracellular levels of TFV-DP and lower circulating levels of TFV than of TDF. The higher TFV-DP levels in peripheral blood mononuclear cells (PBMCs) have resulted in improved antiviral activity at lower doses than TDF in monotherapy studies (11,12). The efficacy of low doses of TAF has been confirmed in phase 2 clinical trials in combination with elvitegravir (EVG, or E), cobicistat (COBI, or C), and emtricitabine (FTC, or F).…”
Section: T Enofovir [(R)-9-(2-phosphonomethoxypropyl)adenine] (Tfv)mentioning
confidence: 87%
“…As expected, the results reported in this paper indicate that TAF is active against PI-R, NNRTI-R, and INSTI-R single-classresistant primary HIV-1 isolates in PBMCs. The two isolates with NRTI-R amino acid substitutions showed only moderately reduced susceptibility to TAF (2.1-and 5.4-fold above that of the wild type) that could possibly be overcome in vivo as a result of the increased TFV-DP level observed in PBMCs upon TAF dosing (2,3). Hypersusceptibility to TAF and/or AZT (2.5-to 10-fold) was noted in INSTI-R and PI-R single-class-resistant mutants in this small data set of HIV-1 primary isolates.…”
Section: Discussionmentioning
confidence: 99%
“…TAF has shown improved safety and pharmacologic profiles, as well as a more potent antiviral effect, compared to the current prodrug of tenofovir (TDF) in early clinical studies (2,3). Treatment of HIVinfected subjects with the 25-mg therapeutic dose of TAF is associated with a 5-fold increase in the quantity of the active moiety, TFV-diphosphate, that is delivered to target cells in vivo compared to treatment with 300 mg TDF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations